Parks as a Tool for HIV Management. (January 2015) - Shacham, Enbal; Hipp, J. Aaron; Scheuermann, Mary; Önen, Nur; Overton, E. Turner
Access to parks improves overall health outcomes in the general population. Given that HIV infection has become a chronic disease to manage, among populations engaged in medical care, parks may be promoted as physical activity opportunities in order to manage chronic comorbid conditions. We conducted a cross-sectional examination of the relationships between sociodemographic and biomedical characteristics to park proximity among 635 individuals receiving outpatient HIV care. The data collected included HIV-related biomarkers, depression, and diagnoses of other chronic diseases. The total acres of parks an individual is exposed within one-quarter mile from their home were assessed. The cohort included 635 individuals (67% men, 73% black, and 21% white, mean age 42 years). Unemployment was negatively associated with park availability. Park proximity was not associated with depression or HIV biomarkers. As yet, little effort has been committed to promoting park usage as a low-cost, sustainable method to addressing comorbidities among individuals with HIV.